Impacts of food and habitat on blood profile of rohu Labeo rohita (Hamilton, 1822) - Wakkas, Saad Abu; Haque, Md Iqramul; Ashaf-Ud-Doulah , Mohammad; Shahjahan, Md (Asian Journal of Medical and Biological Research, 2023)
Food and habitat are important environmental factors, which are play significant role in the physiology of fish. The present experiment was conducted to ascertain the effects of food and habitat on hematological parameters in rohu Labeo rohita reared from first feeding in pond with natural foods and in aquarium using formulated feed for three months (90 days). Fish were sacrificed after the rearing period and hemato-biochemical parameters (hemoglobin - Hb, red blood cell - RBC, white blood cell - WBC and glucose) were measured. Hb (%) of the fish in ponds was slightly higher than in the fish of aquarium. RBC (×106/mm3) in the fish reared in aquaria showed a significant decline in comparison to the pond reared fish, whereas WBC (×103/mm3) showed opposite scenario. Blood glucose was slightly higher in the fish of aquarium than in the fish of pond. The water quality parameters showed no significant difference between the two habitats. The data reported in this study contributes towards the knowledge of hematological evaluation in Labeo rohita and showed that fish food and habitat were crucial in establishing the physiological range supporting the accurate interpretation of hematological parameters for use in examining the health status of this species. Asian J. Med. Biol. Res. 2023, 9 (2), 23-29